PENGARUH PROMOSI (PROMOTION) TERHADAP KEPUTUSAN MAHASISWA BARU MEMILIH PROGAM STUDI MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN KEGURUAN INSTITUT AGAMA ISLAM DARUSSALAM - Mamlukhah Mamlukhah; Yudi Suprastiyo (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2021)
This study aims to determine the effect of promotion on the decision of students to choose the Islamic Education Management Study Program of the Faculty of Tarbiyah and Teachers of the Darussalam Islamic Institute of Academic Year 2019/2020. As one of the factors influencing students' decision to choose a study program, promotion is one of the most important variables in the marketing mix undertaken by a company or educational institution. This research is a quantitative research. This type of research uses quantitative descriptive. Data collection techniques using a questionnaire or questionnaire that has been tested for validity and reliability. To find out whether there is a significant influence between promotion of student decisions in choosing the Islamic Education Management Study Program at the Faculty of Tarbiyah and Teaching Institute of Islamic Religion in the Academic Year 2019/2020 using Pearson's product moment formula. After analyzing the data collected, it was found that (1) the results of the questionnaire were about promotion with 53 respondents classified as very good with the percentage of 88.60% (2) the results of the questionnaire about the student's decision were classified as very good with a percentage of 88.86%. (3) Effect of Promotion on Students' Decisions to Choose Islamic Education Management Study Program of the Tarbiyah and Teaching Faculty of Islamic Republic of Darussalam Academic Year 2019/2020 shows an effect of 90.63%, with the results of t count then 0.935 is between 0.80 - 1,000 Very strong.